IMPLEMENTASI MANAJEMEN PADA PELAYANAN CALON JAMAAH UMRAH DI PT. MULTAZAM WISATA AGUNG CABANG PADANGSIDIMPUAN - Matondang, Ahd Najib; Lubis, Agus Salim; Handayani, Ricka; Putri, Ega (Institut Agama Islam Negeri Metro, 2024)
Service is the main key in a Hajj and Umrah travel service agency. Congregation satisfaction is the starting point for measuring the success and success of a travel agency to label it good or bad. Therefore, this research aims to find out how the management of PT Multazam Wisata Agung Padangsidimpuan branch provides services to prospective Umrah pilgrims. The formulation of this research problem is how to manage services for Umrah candidates at PT. Multazam Wisata Agung Padangsidimpuan Branch? What are the supporting and inhibiting factors for PT. Multazam Wisata Agung Padangsidimpuan Branch in providing Umrah services to its congregation? This research uses a type of field research and uses a qualitative approach, using descriptive methods. This research uses data collection techniques using interview, observation and documentation methods. Then, techniques and data processing and analysis were carried out in 3 stages, namely: Examining all data, data reduction and checking data validation. The results of this research are that the service management carried out by PT. Multazam Wisata Agung Padangsidimpuan Branch towards prospective Umrah pilgrims is responsible and kind. Service management applied in service activities for prospective pilgrims by PT. Multazam Wisata Agung Padangsidimpuan Branch is planning, organizing, implementing and supervising. Services provided include: administration, guidance on Umrah rituals, transportation, accommodation, food and health. The supporting factor in providing services to the congregation is the existence of a good relationship between branch and central management and is also supported by adequate facilities and infrastructure. The inhibiting factor is the large number of travelers engaged in the Hajj and Umrah sector and also the geographical location of PT. Multazam Wisata Agung Padangsidimpuan Branch.